Source of tiny wiggles in Chron C5: A comparison of sedimentary relative intensity and marine magnetic anomalies - (:unkn) unknown (My University, 2003)
In addition to the well-established pattern of polarity reversals, short-wavelength fluctuations are often present in both sea-surface data ("tiny wiggles") and near-bottom anomaly data. While a high degree of correlation between different geographical regions suggests a geomagnetic origin for some of these wiggles, anomaly data alone cannot uniquely determine whether they represent short reversals or paleointensity variations. Independent evidence from another geomagnetic recording medium such as deep-sea sediments is required to determine the true nature of the tiny wiggles. We present such independent evidence in the form of sedimentary relative paleointensity from Chron C5. We make the first comparison between a sedimentary relative paleointensity record (ODP Site 887 at 54°N, 148°W) and deep-tow marine magnetic anomaly data (43°N, 131°W) [Bowers et al., 2001] for Chron C5. The sediment cores are densely sampled at ~2.5 kyr resolution. The inclination record shows no evidence for reverse intervals within the ~1 myr-long normal Chron C5n.2n. Rock magnetic measurements suggest that the primary magnetic carrier is pseudo-single domain magnetite. We choose a partial anhysteretic magnetization (pARM) as our preferred normalizer, and the resulting relative paleointensity record is used as input to a forward model of crustal magnetization. We then compare the results of this model with the stacked deep-tow anomaly records. The two records show a significant degree of correlation, suggesting that the tiny wiggles in the marine magnetic anomalies are likely produced by paleointensity variations. An analysis of our sampling density suggests that if any reverse intervals exist at this site, they are likely to be
Keywords: Miocene relative paleointensity; tiny wiggles; marine magnetic anomalies